(untitled) (Annals of Medical Research, 2021)
Aim: To assess the usefulness of late dimercaptosuccinic acid (DMSA) renal scans in revealing high-grade vesicoureteral reflux (VUR). Material and Methods: Between July 2015 and December 2016, medical records of 112 patients who were admitted with febrile urinary tract infections (fUTIs) were retrospectively reviewed. The demographic information of the patients, and follow-up imaging [ultrasonography (USG), DMSA renal scans, and voiding cystourethrography] data were reviewed.Results: Of the 112 patients, 82 patients (73.2%) were female, 30 were male (26.8%), and the mean age was 7.04 ± 3.94 years. Recurrent fUTIs were detected in 65 patients (58%). Of the patients, 68 (60.7%) had abnormal urinary system USG, and 74 (66.1%) had abnormal DMSA renal scans. Vesicoureteral reflux (VUR) was detected in 63 patients (56.3%). VUR was present in 49 (66.2%) of 74 patients with scarring in DMSA and detected in 14 (38.8%) of 38 patients with normal DMSA scans. Significant agreement (kappa: 0.274 / p=0.003) was found between DMSA and VUR results. The sensitivity, specificity and positive predictive values of late DMSA renal scan to predict VUR were 77.8 %, 49 % and 63.2% respectively.Conclusion: Abnormal late DMSA scans carry a higher sensitivity and positive predictive value for predicting high-grade VUR in children with recurrent fUTIs. Late DMSA imaging seems a useful option in screening for high-grade VUR in children when the acute interventions are limited.